Observasi Laporan Penerapan E-Spt Pph Unifikasi Dan Pph 21 Di Sekretariat Daerah Kabupaten Sleman - Dosroha Elisabet Sipakkar; Rochmad Bayu Utomo (Pusat Riset dan Inovasi Nasional, 2023)
The Directorate General of Taxes (DGT) takes advantage of advances in technology and information systems wich are currently developing rapidly and well. Innovation emerged by creating an application (e-SPT) in the tax administratin system.In the application of e-SPT to the calculation of PPh Unification and PPh 21 at the Regiobal Secretariat of Sleman Regency, it turns out that there are still a few problems that have a negative impact on the individual and the organization. Therefore, this study aims to determine the effect of implementing the e-SPT on calculations on PPh Unification and PPh 21. This survey uses the observation method where I derectly use the e-SPT application and data collection tecniques through experience and records of circumstances. The results of this survey show that there are still errors in the application of the e-SPT to the calculation of PPh Unnification and PPh 21 at the Regional Secretariat of Sleman Regency. This makes my presence very useful to hel employees to be more thorough.The impact of this research is to make employees more careful and at the right time in inputting data.